2020
DOI: 10.1007/s40820-020-00421-5
|View full text |Cite
|
Sign up to set email alerts
|

2D Layered Double Hydroxide Nanosheets and Their Derivatives Toward Efficient Oxygen Evolution Reaction

Abstract: • Synthesis strategies of layered double hydroxides (LDHs) were summarized with classifications of traditional coprecipitation, homogeneous precipitation, and newly developed topochemical oxidation. • Diverse approaches of structural modulation and hybridization to enhance the electrocatalytic activity of LDHs were systematically reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(75 citation statements)
references
References 148 publications
1
72
0
2
Order By: Relevance
“…Balance and optimize the activity and stability of TM LDH nanosheets is also a challenge. [ 120 ] Strategies to elaborately tune the electronic structure and increase the active atoms exposure might be able to address this issue, like topotactic transformation. Recently, topotactically transformed polygonal mesoporous TM LDHs, mediated via metal‐organic framework, exposed abundant under‐coordinated metal centers that lowered the energy barrier of OER and HER.…”
Section: Discussionmentioning
confidence: 99%
“…Balance and optimize the activity and stability of TM LDH nanosheets is also a challenge. [ 120 ] Strategies to elaborately tune the electronic structure and increase the active atoms exposure might be able to address this issue, like topotactic transformation. Recently, topotactically transformed polygonal mesoporous TM LDHs, mediated via metal‐organic framework, exposed abundant under‐coordinated metal centers that lowered the energy barrier of OER and HER.…”
Section: Discussionmentioning
confidence: 99%
“…[ 72 ] Other mechanical exfoliation methods include the use of nitrogen plasma, [ 73,74 ] which works by etching the interlayer anions and disrupting the electrostatic interactions between the host layers. [ 75 ]…”
Section: Modification Of Ldh Photocatalystsmentioning
confidence: 99%
“…The formed vacancy effects on the improvement of charge transfer capability. [59][60][61][62] Additionally, it has been previously reported that when the B:NiFe structure is activated under anodic conditions, it undergoes a structural change reminiscent of the deformation of the NiB i thin lm prepared by electrodeposition. 48 In this step, Jahn-Teller-distorted Ni(III) centers are activated to bisoxo/bridged Ni centers that are organized into sheets of edgesharing octahedral NiO 6 , which is a well-known possible active site for the OER.…”
Section: Characterizations Of Galox-b:nife Ldhmentioning
confidence: 99%